사람중심 기업가정신이 중소기업 성과에 미치는 영향에 관한 연구: 직렬다중매개효과 분석을 중심으로 - 이일한(Lee, II-Han) (벤처창업연구, 2020)
The role of entrepreneurship has become important for the continuous growth (scale-up) of companies in a rapidly changing economic environment. However, research has focused mainly on business-oriented growth that emphasizes efficiency only. However, in the era of the fourth industrial revolution, people have become more important than corporate efficiency. In particular, there are few studies on SMEs. The purpose of this study is to investigate how the characteristics of human - centered organizational culture affects the business ecosystem and firm excellence of SMEs, and how business ecosystem and firm excellence affect the performance of corporations. Therefore, this study focuses on the empathy, enablement, empowerment, and engagement of the corporate culture characteristics of the enterprise and the effects of the independent variables on the business ecosystem and the flower excellence as the parameters and the business ecosystem and company excellence. The main research subjects are the causality analysis that examines the effects on the management performance. The results of the study are as follows. Empathy, enablement, empowerment, engagement have a significant impact on the business ecosystem. In addition, the engagement have a positive effect on firm excellence. The results of empirical studies on the causal relationship between business ecosystem, corporate competence, and company excellence and business performance show that business ecosystem has no statistically significant effect on business performance. Corporate excellence has a significant effect on business performance Respectively. In addition to the above findings, this study can suggest the following implications. First, it is an empirical study of small and medium-sized enterprises (SMEs) by utilizing people-oriented entrepreneurship in addition to existing research. Small and medium-sized enterprises (SMEs) are expected to have lower perceptions of people-oriented management than large corporations or public institutions, but the analysis shows that people-centered entrepreneurship has a significant impact on the business ecosystem. Second, the research results of the serial multiple mediating effect analysis show that the higher the atmosphere of entrepreneurship in a company, the higher the atmosphere of entrepreneurship, and the parameters of business ecosystem and company excellence in the effect of people-oriented entrepreneurship on management performance. It is that the path through which people-oriented entrepreneurship influences management performance was verified by verifying the mediating effect by inputting. Lastly, it is hoped that research on people-oriented entrepreneurship in Korea's SMEs will be activated, providing a theoretical basis for transforming SMEs' business models into innovative types. 급변하는 경제 환경 속에서 기업의 지속적인 성장(Scale-up)을 위해 기업가정신의 역할이 중요해지면서 많은 연구가 이루어지고 있다. 그간의 연구는 효율만을 강조하는 사업 중심의 성장을 주로 다루어 왔다. 그러나 최근 들어 기업 효율성 추구보다는 사람이 더 중요시되고 있는데 반해 사람중심의 기업가정신 특성에 대한 연구는 활발히 진행되지 못하였다. 특히, 중소기업을 대상으로 한 연구는 미비한 실정이다. 이에 본 연구에서는 사람중심 기업가정신 특성이 중소기업의 비지니스 생태계와 회사탁월성에 어떠한 영향을 미치는지, 비지니스 생태계와 회사탁월성은 기업성과에 어떤 영향을 주는지를 연구하는데 목적이 있다. 따라서 본 연구는 기업의 사람중심 기업가정신 특성을 공감, 역량개발, 권한위임, 업무몰입도로 구분하고 각각의 독립변수들이 매개변수인 비지니스 생태계와 화사탁월성에 미치는 영향과 비지니스 생태계와 회사탁월성이 경영성과에 미치는 영향을 살펴보는 인과관계 분석이 주된 연구대상이다. 연구의 결과를 자세히 제시하면 다음과 같다. 사람중심 기업가정신 특성과 비지니스 생태계 간의 인과관계에 대한 실증 연구결과를 요약하면 공감, 역량개발, 권한위임, 업무몰입도는 비지니스 생태계에 유의한 영향을 미치는 것으로 나타났다. 사람중심 기업가정신 특성과 회사탁월성 간의 인과관계에 대한 실증 연구결과를 요약하면 업무몰입도는 회사탁월성에 유의한 영향을 미치는 것으로 나타났으며, 공감, 역량개발, 권한위임은 통계적으로 회사탁월성에 유의한 영향을 미치지 않는 것으로 나타났다. 기업역량인 비지니스 생태계와 회사탁월성과 경영성과 간의 인과관계에 대한 실증 연구결과를 요약하면, 비지니스 생태계는 경영성과에 통계적으로 유의한 영향을 미치지 않는 것으로 나타났으며, 회사탁월성은 경영성과에 유의한 영향을 미치는 것으로 나타났다. 또한, 추가분석에서 사람중심 기업가정신이 회사탁월성을 거쳐 경영성과에 미치는 개별매개 효과는 통계적으로 유의한 효과를 가지는 것으로 나타났으며, 사람중심 기업가정신이 비지니스 생태계와 회사탁월성을 경유하여 경영성과에 미치는 개별매개효과가 나타났다. 이상의 연구결과와 함께 본 연구를 통해 다음과 같은 시사점을 제시할 수 있다. 첫째, 기존연구와 더불어 사람중심 기업가정신을 활용하여 중소기업을 대상으로 실증연구 했다는 점이다. 중소기업은 대기업이나 공공기관보다 사람중심 경영에 대한 인식이 낮을 것으로 추측되었으나 분석결과 사람중심 기업가정신이 비지니스 생태계에 큰 영향을 미치고 있음을 확인하였다는데 큰 의미가 있다고 하겠다. 둘째, 직렬 다중매개효과 분석의 연구결과는 기업에서 사람지향성의 분위기가 높을수록 기업가 지향성의 분위기도 높아지는 경향이 있으며, 사람중심 기업가정신이 경영성과에 미치는 영향에 있어 비지니스 생태계와 회사탁월성이라는 매개변수를 투입하여 매개효과를 검증함으로써 사람중심 기업가정신이 경영성과에 영향력을 미치는 경로를 확인하였다는 점이다. 마지막으로 우리나라 중소기업에 대한 사람중심 기업가정신에 대한 연구가 활성화되어 중소기업의 사업모델이 혁신형으로 전환하는데 이론적 기반을 제공할 수 있기를 기대해 본다.